A Fuzzy TOPSIS with Z-Numbers Method for Assessment on Memorandum of Understanding at University - Yahia Awajan, Khaleel; Zamri, Nurnadiah (International Journal of Engineering and Technology, 2026)
Memorandum of Understanding (MOU) is the signing an agreement between university with other university. It has been known as the policy that sharing different competencies in academic between both Universities’ involved. Classifying the issues on choosing the suitable university, involves a proportion of vague and uncertain cases. Fuzzy Z-numbers gives more uncertainties compared to Fuzzy Sets (FSs). They provide us with additional degree of freedom to represent the uncertainty and fuzziness in real situations. The objective of this paper is to apply a FTOPSIS with Z-numbers to handle uncertainty for the Memorandum of Understanding Case. Five criteria and three alternatives are used to evaluate the decision from the university’s expert. From the result, it reveals that the FTOPSIS with Z-numbers offers us with another suitable way to handle FMCDM problems in a more intelligent and flexible way due to the fact that it uses FTOPSIS with Z-numbers.